Optimization of magnetoimpedance effect in Co-based ribbon by laser patterning for sensor arrays application. (10th January 2018) - Zhao, Chenbo; Pan, Lining; Li, Xiaolei; Ma, Lei; Liu, Qingfang; Wang, Jianbo
Abstract: The giant magnetoimpedance (GMI) effect in Co-based ribbon with different patterning structures, named series structure (SS), parallel structure (PS) and cross structure (CS) with different angle, has been investigated. Absolute variation of impedance and GMI ratio (154% for sample SS, 220% for sample PS and 236% for sample CS at 5 MHz) in different patterning structures have been evaluated comprehensively. The double-peak GMI curves with a spindle-shape embossment are observed in sample PS and CS, which could be attributed to coupling effect between the strips and the especial geometry shape of samples. The enhancement of GMI effect in different patterning structures is attributed to different complex magnetic interaction. The results are beneficial for sensor arrays for measurement of weak magnetic fields.